VISIR deployment in undergraduate engineering practices - Tawfik, Mohamed (2011)
Practical sessions are the backbone of qualification in engineering education. It leads to a better understanding and allows mastering scientific concepts and theories. The lack of the availability of practical sessions at many universities and institutions owing to the cost and the unavailability of instructors the most of the time caused a significant decline in experimentation in engineering education over the last decades. Recently, with the progress of computer-based learning, remote laboratories have been proven to be the best alternative to the traditional ones, regarding to its low cost and ubiquity. Some universities have already started to deploy remote labs in their practical sessions. This contribution compiles diverse experiences based on the deployment of the remote laboratory, Virtual Instrument Systems in Reality (VISIR), on the practices of undergraduate engineering grades at various universities within the VISIR community. It aims to show the impact of its usage on engineering education concerning the assessments of students and teachers as well.